Visceral Adiposity Is an Independent Determinant of Hypercoagulability as Measured by Thrombin Generation in Morbid Obesity - Chitongo, P. B.; Roberts, L. N.; Yang, L.; Patel, R. K.; Lyall, R.; Luxton, R.; Aylwin, S. J. B.; Arya, R. (TH Open, 2017)
Introduction Increased visceral adipose tissue (VAT) has been shown to be associated with the development of insulin resistance, type 2 diabetes, stroke, and ischemic heart disease. It remains unknown whether fat distribution impacts on coagulation markers and/or the risk of venous thrombosis. This study evaluates markers of hypercoagulability in class III obesity (body mass index [BMI] >40 kg/m2) compared with nonobese controls. We further investigated whether hypercoagulability was influenced by VAT, metabolic syndrome, and metabolic markers, including adiponectin.Patients and Methods Ninety patients were recruited from the obesity clinic at King's College Hospital from November 2009 to December 2011. The inclusion criteria were class III obesity (BMI ≥40 kg/m2) and age 18 to 65 years. A control group (healthy ambulatory participants, with a BMI < 30 kg/m2) was recruited from volunteers responding to advertisement. Abdominal VAT and subcutaneous adipose tissue surface areas were determined by evaluation of a single-slice CT at spinal vertebra L4.Results Thrombin generation revealed a significantly increased peak and endogenous thrombin potential in patients compared with controls. Lag time and time to peak (ttP) were also significantly prolonged in patients. VAT was found to have the strongest association with thrombin generation parameters: lag time (β = 0.378; p < 0.001), peak thrombin (0.378; p = 0.04), and ttP (β = 0.373; p = 0.001). BMI was found to be a predictor for lag time only (β = 0.313; p = 0.003). SAT was not associated with any of the thrombin generation parameters (data not shown). VAT was found to be an independent determinant of peak thrombin, lag time, and ttP. The study suggests not only fat mass but also fat distribution, particularly visceral adiposity, mediates hypercoagulability in obesity.
Keywords: coagulation factors; visceral adipose tissue; hemostatic marker; tissue factor pathway inhibitor; venous thrombosis